Peripheral Blood Lymphocyte Subsets (CD4(+), CD8(+) T Cells, NK Cells) in Patients with Cardiovascular and Neurological Complications after Carotid Endarterectomy - Kotfis, Katarzyna (Int J Mol Sci, 2015)
Background: The aim of the study was to evaluate the differences in the circulating immune cells’ subgroups after the atherosclerotic plaque removal in patients presenting with postoperative complications as compared to the patients without complications after carotid endarterectomy (CEA). Methods: Patients with significant carotid atherosclerosis (n = 124, age range: 44 to 87 years) who underwent CEA were enrolled in a prospective study. The immunology study using flow cytometry was performed to determine the percentages of peripheral blood T cells (CD4(+), CD8(+), Treg—CD4(+)/CD25(+)) and NK (natural killer) cells before and after the procedure. The data were expressed as the percentage of total lymphocytes ± the standard error of mean. Results: The mean percentage of lymphocytes (61.54% ± 17.50% vs. 71.82% ± 9.68%, p = 0.030) and CD4 T lymphocytes (T helper, 38.13% ± 13.78% vs. 48.39% ± 10.24%, p = 0.027) was significantly lower six hours after CEA in patients with postoperative 30-day cardiovascular and neurological complications as compared to the group without complications. On the other hand the mean NK level in the group with complications was significantly higher (21.61% ± 9.00% vs. 15.80% ± 9.31%, p = 0.048). Conclusions: The results of this study suggest that after carotid endarterectomy the percentages of circulating immune cells subsets differ in patients with and without postoperative complications.